The Chances of Survival for Breast Cancer Patients - Ardwichai, Phirada; Choodum, Natthawirot (Journal of The Royal Thai Army Nurses, 2024)
The survival rate of breast cancer patients depends on many factors, including age, body mass index, physical condition of the cancer patient, type of breast cancer, chemotherapy regimen for metastatic breast cancer treatment, and treatment goals for metastatic breast cancer patients. The above factors result in different survival rates for cancer patients depending on the stage of diagnosis. For example, stage 1, most cancer patients have a survival rate of 5 years or more after diagnosis. Stage 2, 90 percent have a survival rate of 5 years or more after diagnosis. Stage 3, more than 70 percent have a survival rate of 5 years or more after diagnosis. Stage 4, more than 25 percent have a survival rate of 5 years or more after diagnosis. Breast cancer cannot be cured, but it can be controlled with treatment. The current treatment that is accepted as being able to cure and make patients survive for a long time is targeted therapy and cell therapy. However, the chance of survival, whether it is higher or lower than the above, may depend on the factors of the breast cancer patient themselves, especially their physical, mental, and family support, which are the main factors in increasing the chance of survival.